Investigating neuropsychological dysfunction in soccer players. - Weldon, Quentin George (My University, 1998)
This study sought to investigate the incidence and severity of disruptions of cognitive functioning in children following exposure to soccer play. (Abbreviation abstract)
A Dissertation submitted to the Faculty of arts of the University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Master of Arts (Research Psychology).
Keywords: Cognition disorders.; Soccer players -- South Africa.